Senam Sendi Bagi Penderita Asam Urat Di Rt 06 Kelurahan Ponorogo Kecamatan Lubuklinggau Utara II - Nora, Eis Sian; Subakti, Alan; Susanti, Eva; Kusmira, Devi; Larasati, Nur Dwi; Rohani, Tuti; Azissah, Danur; Murwati, Murwati (Jurnal Dehasen Mengabdi, 2025)
Joint gymnastics is a complementary therapy that can help reduce pain and increase joint flexibility for people with gout arthritis (gout). This journal discusses the effectiveness of joint exercises in improving the quality of life of people with gout, the method of implementing the exercises, and the benefits obtained from this exercise. Based on the results of community service activities in RT 06 Ponorogo Village, joint exercises are proven to help reduce pain and increase the flexibility of the participants' joints